ISOLATION AND IN SILICO CHARACTERIZATION OF GERANIOL DEHYDROGENASE ENCODING GENE USING MODIFIED DNA EXTRACTION PROTOCOL FROM AMERICAN BASIL (OCIMUM AMERICANUM L.) - AAKANKSHA WANY; ASHUTOSH KUMAR; VINOD KUMAR NIGAM; DEV MANI PANDEY (International Journal of Pharma and Bio Sciences, 2013)
The present study deals with the identification, isolation and in silico characterization of gene encoding geraniol dehydrogenase from Ocimum americanum. Mature leaves of plants have a higher degree of secondary metabolites that hampers the nucleic acid isolation, PCR amplification and other downstream reactions. The DNA isolation from mature leaves of O. americanum is described here which involves a modified cetyl trimethyl ammonium bromide extraction protocol (3.5%) with high salt concentration to remove polysaccharides, 3% poly vinyl pyrrolidone to remove polyphenols and an extended RNase treatment. This protocol yielded genomic DNA having high quality as well as quantity. Gene specific primers were designed using Primer3 tool, amplified through PCR and sequenced. In silico characterization and annotation of geraniol dehydrogenase was completed by web based tools. The newly constructed 1647 bp length sequence was submitted in NCBI (GenBank Id: JQ765502.1) and named Ocimum americanum geraniol dehydrogenase (OaGDH) gene.